Nicarbazin as an oral contraceptive in eared doves - Olivera, Lourdes; Pereyra, Silvia; Banchero, Georgget; Tellechea, Guillermo; Sawchik, Jorge; Avery, Michael L.; Rodríguez, Ethel (DigitalCommons@University of Nebraska - Lincoln, 2021)
Eared doves (Zenaida auriculata) are responsible for substantial losses in cereal and oil crops as well as in dairy and feedlot production in the southern cone of South America. Various strategies have been shown to be effective in reducing damage at the farm scale, but in some scenarios, it is necessary to also incorporate population control methods due to excessive bird population size. An alternative approach to reduce pest bird populations is the use of contraceptive methods, minimizing the impact on the environment and non-target populations. Nicarbazin is registered in the United States as a contraceptive for Branta canadensis and Columba livia. The aim of this study was to measure the effect of nicarbazin on the reproductive performance of eared doves in captivity. This study included eleven caged pairs of nesting eared doves in three experimental phases (pre-treatment, treatment, recovery). Each pair was exposed to nicarbazin bait for 4 h per day. The contraceptive used was OvoControlP® (0.5% nicarbazin) ground with a millstone into particles of 0.5–3.0 mm. Daily bait consumption and reproductive variables per pair (egg laying and 14-day-old fledgling) were recorded, and levels of 4,4′dinitrocarbanilide were measured in feces and unhatched eggs. Median consumption was 4.2 g of bait/pair/day. We observed a 62% reduction in the number of viable eggs and successful nestlings in the treatment phasein contrast to pre-treatment (V = 36; p = 0.006). There were no significant differences (V = 0; p = 1) in the number of viable eggs between the pretreatment and recovery phases. Median daily bait consumption by pairs producing zero or one nestling (4.4 and 5.0 g/pair/day respectively) was significantly higher than that of pairs that had two nestlings (3.4 g/pair) during the treatment phase (t = 2.0; p = 0.002). Nicarbazin was effective in reducing reproductive performance of eared doves, and its effect was reversible when the treatment finished.